Protein Hydrolysate or Plant Extract-based Biostimulants Enhanced Yield and Quality Performances of Greenhouse Perennial Wall Rocket Grown in Different Seasons - Gianluca Caruso; Stefania De Pascale; Eugenio Cozzolino; Maria Giordano; Christophe El-Nakhel; Antonio Cuciniello; Vincenzo Cenvinzo; Giuseppe Colla; Youssef Rouphael (Plants, 2019)
Research has been increasingly focusing on the environmentally friendly biostimulation of vegetable crop performances under sustainable farming management. An experiment was carried out in southern Italy on Diplotaxis tenuifolia to assess the effects of two plant biostimulants (Legume-derived protein hydrolysate, Trainer®; Tropical plant extract, Auxym®) and a non-treated control, in factorial combination with three crop cycles (autumn−winter; winter; and winter−spring) on leaf yield, photosynthetic and colour status, quality, elemental composition, antioxidant content and activity. Both biostimulants prevalently contain amino acids and soluble peptides, showing the major effects on crop performances, though Auxym also has a small percentage of phytohormones and vitamins. The biostimulants enhanced plant growth and the productivity of perennial wall rocket. The winter−spring cycle led to higher leaf yield than the winter one. The two plant biostimulants enhanced leaf dry matter, oxalic and citric acids, Ca and P concentrations, phenols and ascorbic acid content as well as antioxidant activity, but did not increase nitrate content. A presumed mechanism involved in the enhancement of crop production could be attributed to the improvement of mineral nutrient availability and uptake. The winter−spring cycle elicited higher antioxidant content and activity than winter crops. Our current study shows that both the legume-derived protein hydrolysate and tropical plant extract represent an effective tool for boosting the yield, nutritional and functional quality of vegetable produce in the view of sustainable crop systems.